PENGARUH LINGKUNGAN KERJA FISIK DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN PRODUKSI PT DANINDO TAPE PACKAGING INDUSTRY - Dapit Dapit; Gustia Wardani, Windy (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of Physical Work Environment and Employee Satisfaction on Turnover Intention in Production Employees of PT Danindo Tafe Packaging Industry. The type of research is associative with a quantitative approach. The research sample is 58 respondents. The data analysis method used in the study includes instrument testing consisting of validity, reliability, classical assumption testing consisting of (normality, multicollinearity, and heteroscedasticity tests), multiple linear regression tests, correlation coefficients, coefficients of determination (R²), hypothesis testing consisting of partial t-tests and simultaneous f-tests. The research results indicate that, partially, the Physical Work Environment has an influence on Turnover Intention, with a significance value of 0.000 < 0.05 and a regression coefficient of 0.536. Employee Satisfaction also has a positive and significant influence on Turnover Intention, with a significance value of 0.000 < 0.05 and a regression coefficient of 0.376. The R-squared value indicates that the physical work environment and Employee Satisfaction together contribute 50.3% to Turnover Intention, while the remaining 49.7% is influenced by other factors or variables not examined